A Human CD68 Promoter-Driven Inducible Cre-Recombinase Mouse Line Allows Specific Targeting of Tissue Resident Macrophages - Rumianek, Agata N.; Davies, Ben; Channon, Keith M.; Greaves, David R.; Purvis, Gareth S. D. (Frontiers in Immunology, 2022)
Current genetic tools designed to target macrophages in vivo often target cells from all myeloid lineages. Therefore, we sought to generate a novel transgenic mouse which has a tamoxifen inducible Cre-recombinase under the control of the human CD68 promoter (hCD68-CreERT2). To test the efficiency and specificity of the of Cre-recombinase activity we crossed the hCD68-CreERT2 mice with a loxP-flanked STOP cassette red fluorescent protein variant (tdTomato) mouse. We established that orally dosing mice with 2 mg of tamoxifen for 5 consecutive days followed by a 5-day induction period resulted in robust expression of tdTomato in CD11b+ F4/80+ tissue resident macrophages. Using this induction protocol, we demonstrated tdTomato expression within peritoneal, liver and spleen macrophages and blood Ly6Clow monocytes. Importantly there was limited or no inducible tdTomato expression within other myeloid cells (neutrophils, monocytes, dendritic cells and eosinophils), T cells (CD4+ and CD8+) and B cells (CD19+). We also demonstrated that the level of tdTomato expression can be used as a marker to identify different populations of peritoneal and liver macrophages. We next assessed the longevity of tdTomato expression in peritoneal macrophages, liver and splenic macrophages and demonstrated high levels of tdTomato expression as long as 6 weeks after the last tamoxifen dose. Importantly, hCD68-CreERT2 expression is more restricted than that of LysM-Cre which has significant expression in major myeloid cell types (monocytes and neutrophils). To demonstrate the utility of this novel macrophage-specific Cre driver line we demonstrated tdTomato expression in recruited CD11b+CD64+F4/80+ monocyte-derived macrophages within the atherosclerotic lesions of AAV8-mPCSK9 treated mice, with limited expression in recruited neutrophils. In developing this new hCD68-CreERT2 mouse we have a tool that allows us to target tissue resident macrophages, with the advantage of not targeting other myeloid cells namely neutrophils and inflammatory monocytes.